Elements of Effective Interventions for Addressing Intimate Partner Violence in Latina Women: A Systematic Review - Alvarez, Carmen P.; Davidson, Patricia M.; Fleming, Christina; Glass, Nancy E. (PloS one, 2016)
Intimate partner violence remains a global problem and is of particular concern in Latina diasporas. To identify effective elements of interventions to address intimate partner violence in Latina women. The systematic review was undertaken according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We focused the search on intervention studies assessing intimate partner violence as an outcome measure and on publications in English and Spanish from the last 11 years (2004-2015). Despite the scope of the problem, from the 1,274 studies screened only four met the search criteria and only a single study included an exclusive Latino population. Of the four interventions, one was only as effective as the control treatment. Heterogeneity of study populations and designs prohibited meta-analytic methods. Theoretically derived interventions that are gender specific, culturally appropriate, target mutual aid through group dynamics, and that are developed collaboratively with the target population are likely to be most effective.